A measurement model of the determinants of financial exclusion among micro-entrepreneurs in Ilorin, Nigeria - Adewale, Abideen Adeyemi (2011)
This study investigated the various factors that impede both the access to and use of the requisite financial resources for entrepreneurial development in Nigeria. Data was collected via a survey questionnaire administered on micro-entrepreneurs in Ilorin, Kwara State, Nigeria. A measurement model using the structural equation modeling approach was adopted. The paper concluded that both the voluntary and involuntary financial exclusion factors significantly account for financial exclusion in Nigeria. However, voluntary exclusion signals more problem. This is because it is a reflection of lack of use, rather than lack of access to financial services by the poor.